Analysis of tribological behaviour of aluminum‐titanium carbide‐basalt metal matrix composite. Issue 11 (12th November 2021) - Muthu, P.
Abstract: In the recent years, particulate reinforced aluminum based matrix composites are playing an important role in automobile and aerospace applications due to their enhanced properties. In this work, an attempt has been made to optimize the tribological behaviour of aluminum 7075 matrix reinforced with titanium carbide (3 percent weight) and basalt particles (2 percent weight) using Taguchi based grey relational analysis. Composites are fabricated according to american society for testing materials standard using stir casting method dry sliding wear tests were carried out using pin on disc apparatus as per Taguchi's L9 orthogonal array. Grey relational analysis was used to obtain the optimum process parameters for multiple quality characteristics such as wear rate and coefficient of friction. Then significant contribution of wear parameters was determined by analysis of variance. A confirmatory test was carried out to validate the test result. Finally, the micro structural investigation on the worn surfaces was performed by scanning electron microscope. Abstract : From the value of grey relational grade, the factor effects are plotted. Since the grey relational grade represents the level of correlation between the reference sequence and the comparability sequence, the greater value of the grey relational grade means that the comparability sequence has a stronger correlation to the reference sequence.